Proteomic and metabolomic basis for improved textural quality in crisp grass carp (Ctenopharyngodon idellus C.et V) fed with a natural dietary pro-oxidant. (30th September 2020) - Yu, Ermeng; Fu, Bing; Wang, Guangjun; Li, Zhifei; Ye, Dewei; Jiang, Yong; Ji, Hong; Wang, Xia; Yu, Deguang; Ehsan, Hashimul; Gong, Wangbao; Zhang, Kai; et al.
Highlights: Dietary pro-oxidant improved the textural quality of grass carp muscle. ROS likely disturbed actin-myosin interaction and collagen turnover in the muscle. ROS suppressed carbohydrate metabolism and enhanced fatty acid oxidation. Abstract: Reactive oxygen species (ROS) regulate metabolism and chemical composition of various tissues. To understand how ROS affect the textural quality of fish muscle, we performed a multi-omics analysis on an established crisp grass carp model fed with a natural pro-oxidant faba bean. ROS levels were systemically and significantly increased up to three-fold in crisp grass carp, improving the muscle texture. Lipid metabolism was significantly enhanced up to five-fold in muscle and liver possibly to compensate the impaired carbohydrate metabolism of these tissues, but this caused further local ROS production. Mitochondrial damage associated with autophagy was evident in crisp grass carp. Proteomics revealed that elevated ROS likely disturbed the actin-myosin interaction and collagen turnover inducing fragmentation of myofibrillar proteins, all of which could have positively impacted the textural quality. The systemic metabolic changes that lead to the partial collapse of redox regulation likely underlie the ROS-induced improvement of textural quality.